2020
DOI: 10.1186/s12915-020-00892-3
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the past, present and future research landscape of paternal effects

Abstract: Background Although in all sexually reproducing organisms an individual has a mother and a father, non-genetic inheritance has been predominantly studied in mothers. Paternal effects have been far less frequently studied, until recently. In the last 5 years, research on environmentally induced paternal effects has grown rapidly in the number of publications and diversity of topics. Here, we provide an overview of this field using synthesis of evidence (systematic map) and influence (bibliometri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 498 publications
0
32
0
Order By: Relevance
“…In contrast, paternal effects were initially thought to be minimal or non-existent (Roach and Wulff, 1987). However, increased interest on paternal effects in recent years (Rutkowska et al, 2020) has revealed evidence that non-genetic paternal effects can arise in both mammals and fish through changes in the sperm epigenome and transmission of the paternal DNA methylome that directly affect resulting offspring through DNA methylation (Jiang et al, 2013;Baxter and Drake, 2019;Skvortsova et al, 2019). Effects of epigenetic transfer can be wide ranging, for example, male rats conditioned to fear the smell of acetophenone paired with naive females had produced offspring that also showed an aversion to the same odor (Dias and Ressler, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, paternal effects were initially thought to be minimal or non-existent (Roach and Wulff, 1987). However, increased interest on paternal effects in recent years (Rutkowska et al, 2020) has revealed evidence that non-genetic paternal effects can arise in both mammals and fish through changes in the sperm epigenome and transmission of the paternal DNA methylome that directly affect resulting offspring through DNA methylation (Jiang et al, 2013;Baxter and Drake, 2019;Skvortsova et al, 2019). Effects of epigenetic transfer can be wide ranging, for example, male rats conditioned to fear the smell of acetophenone paired with naive females had produced offspring that also showed an aversion to the same odor (Dias and Ressler, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Paternal effects have received less attention relative to maternal effects (Rutkowska et al ., 2020) and the size of the epigenetic paternal contribution to such changes relative to the maternal contribution is still debated (reviewed by Best et al ., 2018). In the few studies that have tested relative parental contributions to TGP in metabolic traits in fish, the paternal contribution is either less than (Shama et al ., 2014) or comparable to the maternal contribution (Penney et al ., in press).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that brook trout are capable of WGP and TGP responses to environmental temperatures, and that TGP would enhance upper thermal tolerance. To date, parental contributions to TGP have largely focused on the maternal environment which is thought to have a larger effect on offspring than the paternal environment (Shama et al ., 2014; Best et al ., 2018); however, paternal contributions are increasingly being reported across taxa (Hellman et al ., 2020; Rutkowska et al ., 2020). Our experimental design provided us with the opportunity to assess both maternal and paternal contributions to offspring thermal responses.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in sticklebacks, exposure to predators induces grand-paternal effects that also differ by offspring sex (Hellmann et al 2020). Such multigenerational examples of transgenerational plasticity could have very interesting implications for phenotypic variation and adaptive evolution (discussed below), but relatively few experimental studies have investigated the potential for transgenerational plasticity to persist over more than two generations, or for environmental effects that act over multiple generations to accumulate and interact (Rutkowska et al 2020). The proximate mechanisms that mediate the transmission of environmental effects across multiple generations remain poorly understood, although considerable progress in the understanding of such mechanisms has come from work on nematode worms (Greer et al 2010;Greer et al 2011;Klosin et al 2017;Rechavi and Lev 2017).…”
Section: The Stability Of Transgenerational Plasticitymentioning
confidence: 99%